The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.ijhydene.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Study on Sm1.8Ce0.2CuO4–Ce0.9Gd0.1O1.95 composite cathode materials for intermediate temperature solid oxide fuel cell

Abstract: Sm1.8Ce0.2CuO4-xCe0.9Gd0.1O1.95 (SCC-xCGO, x = 0-12 vol.%) composite cathodes supported on Ce0.9Gd0.1O1.95 (CGO) electrolyte are studied for applications in IT-SOFCs. Results show that Sm1.8Ce0.2CuO4 material is chemically compatible with Ce0.9Gd0.1O1.95 at 1000 °C. The composite electrode exhibits optimum microstructure and forms good contact with the electrolyte after sintering at 1000 °C for 4 h. The polarization resistance (Rp) reduces to the minimum value of 0.17 Ω cm 2 at 750 °C in air for SCC-CGO06 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…[ 342 ] In another case, a Sm 1.8 Ce 0.2 CuO 4 -Ce 0.9 Gd 0.1 O 1.95 composite cathode materials was prepared and an enhanced electrode performance was also observed as compared with the performance of a pure Sm 1.8 Ce 0.2 CuO 4 electrode. [ 343 ] It seemed that improving ionic conductivity of the Sm 1.8 Ce 0.2 CuO 4 electrode could promote its activity for ORR. However, the main drawback of Nd 2 CuO 4 and Sm 2 CuO 4 materials for application in SOFCs was their low electrical conductivities (less than 1 S cm −1 ) at working temperature.…”
Section: Ruddlesden-popper-type Metal Oxidesmentioning
confidence: 99%
“…[ 342 ] In another case, a Sm 1.8 Ce 0.2 CuO 4 -Ce 0.9 Gd 0.1 O 1.95 composite cathode materials was prepared and an enhanced electrode performance was also observed as compared with the performance of a pure Sm 1.8 Ce 0.2 CuO 4 electrode. [ 343 ] It seemed that improving ionic conductivity of the Sm 1.8 Ce 0.2 CuO 4 electrode could promote its activity for ORR. However, the main drawback of Nd 2 CuO 4 and Sm 2 CuO 4 materials for application in SOFCs was their low electrical conductivities (less than 1 S cm −1 ) at working temperature.…”
Section: Ruddlesden-popper-type Metal Oxidesmentioning
confidence: 99%
“…We studied the electrochemical performance of Sm 2−x Ce x CuO 4 and the ASR of Sm 1.8 Ce 0.2 CuO 4 was found to be 1.16 Ω cm 2 at 700 °C [17]. Further research on the oxygen reduction kinetics of these cuprate cathodes always found that the charge transfer reaction was the rate limiting step [16], [17], [18], [19] and [20]. Thus, enhancing the oxygen reduction activity of these cathode materials is crucial for the development of novel IT-SOFC cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Many cobalt-containing perovskite oxides (like Sm0.5Sr0.5CoO3-δ [6][7][8], La1-xSrxCoO3-δ [9][10][11][12][13][14], La1-xSrxCo1-yFeyO3-δ [15,16], Ba1-xSrxCo1-yFeyO3-δ [17][18][19]) have been developed as cathode materials for intermediate temperature range (500-700 ℃), which demonstrate that excellent ionic and electronic conductivities extend the triple-phase boundary (TPB) region from the cathodeelectrolyte interface into the bulk of the cathode. The powders of these cathode materials are made typically by sol-gel [20][21][22], solid state [23][24][25], combustion [26][27][28], acetic-acrylic [5,29,30], citric acid-EDTA [4,9,10,16,31], solid-liquid [32][33][34][35] etc.…”
Section: Introductionmentioning
confidence: 99%